2005
DOI: 10.1161/01.cir.0000161797.67671.a7
|View full text |Cite
|
Sign up to set email alerts
|

Weight Gain in the First Week of Life and Overweight in Adulthood

Abstract: Background-Successful prevention of obesity and related cardiovascular risk factors requires a clear understanding of its determinants over the life course. Rapid infancy weight gain is associated with childhood obesity, whereas low infancy weight is associated with coronary heart disease. Our aim was to identify during which periods in infancy weight gain is associated with adult obesity. Methods and Results-A cohort of European American formula-fed subjects, measured on 7 occasions during infancy as part of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
130
4
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 383 publications
(146 citation statements)
references
References 44 publications
9
130
4
3
Order By: Relevance
“…In formula-fed infants weight gain in the first 8 d of life was shown to be associated with the risk of being categorised as obese in early adulthood (Stettler et al 2005). Consistent with these data, weight gain in the first 2 weeks of postnatal life in preterm infants was found to be associated with insulin resistance during adolescence (Singhal et al 2003a).…”
Section: Postnatal Growth and Subsequent Body Compositionsupporting
confidence: 60%
“…In formula-fed infants weight gain in the first 8 d of life was shown to be associated with the risk of being categorised as obese in early adulthood (Stettler et al 2005). Consistent with these data, weight gain in the first 2 weeks of postnatal life in preterm infants was found to be associated with insulin resistance during adolescence (Singhal et al 2003a).…”
Section: Postnatal Growth and Subsequent Body Compositionsupporting
confidence: 60%
“…There is now increasing evidence that a rapid growth (weight and/or length) in infancy or early childhood can predispose to later risks. 26 It is associated with large subsequent weight gain 17,23,24,54 and a central body fat pattern 23,25 and also with a risk of diabetes, 55 cardiovascular disease 56 and cancer. 57,58 Paradoxically, the proportion of fat in the infant diet is low at a period of high energy needs.…”
Section: Factors Associated With An Early Ar and Increased Fatnessmentioning
confidence: 99%
“…This theory was a matter of controversy and has not been pursued. Nevertheless, some recent epidemiological studies have demonstrated a correlation between the rates of weight gain during the first 4 months, 16 even the first week of life, 17 and prevalence of overweight later in life. These findings could renew interest in the 'adipocyte-number hypothesis' and the influence of diet during early life on adipose tissue development.…”
Section: Adipose Tissue Development In Infancymentioning
confidence: 99%